2020
DOI: 10.3390/jcm9010167
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Renal Function and Adverse Clinical Events in Patients with Atrial Fibrillation: A Japanese Multicenter Registry Substudy

Abstract: Background: Atrial fibrillation (AF) and chronic kidney disease (CKD) often coexist, but the real-world data after approval of direct oral anticoagulants (DOACs) are still lacking in Japan. We investigated the association of the baseline renal function and adverse clinical events and risk of adverse clinical events with DOACs compared to warfarin for each renal functional level in Japanese AF patients. Methods: The present substudy was based on the SAKURA AF Registry, a Japanese multicenter observational regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…Most recently, a prospective Garfield‐AF Registry (Goto et al, 2019 ) including 35 countries and over 33,000 patients showed moderate‐to‐severe CKD was independently associated with mortality in newly diagnosed AF, and this effect is even greater in patients from Asia than the rest of the world. Another Japanese registry study (Yuzawa et al, 2020 ) also showed that an impaired renal function was significantly associated with all adverse events in AF patients (CrCl < 50 ml/min vs. CrCl≥80 ml/min, adjusted HR s: 2.53 for death, 2.53 for cardiovascular events).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Most recently, a prospective Garfield‐AF Registry (Goto et al, 2019 ) including 35 countries and over 33,000 patients showed moderate‐to‐severe CKD was independently associated with mortality in newly diagnosed AF, and this effect is even greater in patients from Asia than the rest of the world. Another Japanese registry study (Yuzawa et al, 2020 ) also showed that an impaired renal function was significantly associated with all adverse events in AF patients (CrCl < 50 ml/min vs. CrCl≥80 ml/min, adjusted HR s: 2.53 for death, 2.53 for cardiovascular events).…”
Section: Discussionmentioning
confidence: 90%
“…The presence of renal dysfunction in AF patients was associated with a substantial increase in TE incidence and an increased risk of bleeding events (Potpara et al, 2018 ). Previous studies already demonstrated that moderate to severe renal impairment increased the risk of bleeding in AF patients (Abe et al, 2017 ; Banerjee et al, 2014 ; Cho et al, 2017 ; Yuzawa et al, 2020 ), but some other studies showed diffident results, renal impairment was not a risk factor for bleeding (Boriani et al, 2016; Kodani et al, 2018 ). This study showed renal dysfunction was not an independent predictor for major bleeding.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As renal function declines, patients are at an increasing risk of thrombosis, bleeding and death [29,30]. From the pivotal phase III DOAC trials in VTE and NVAF, DOACs have been deemed safe and effective in patients with CKD stages 1-3; however, these RCTs excluded patients with creatinine clearance (CrCl) less than 25-30 ml/min [31].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%